2016
DOI: 10.5194/acp-16-13725-2016
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of oceanic whitecap fraction based on satellite observations

Abstract: Abstract. In this study, the utility of satellite-based whitecap fraction (W ) data for the prediction of sea spray aerosol (SSA) emission rates is explored. More specifically, the study aims at evaluating how an account for natural variability of whitecaps in the W parameterization would affect SSA mass flux predictions when using a sea spray source function (SSSF) based on the discrete whitecap method. The starting point is a data set containing W data for 2006 together with matching wind speed U 10 and sea … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 82 publications
0
26
0
Order By: Relevance
“…This could potentially explain the difference between the value of c 1 we retrieved from our measurements and the one retrieved from the entire whitecap database. However, conversely, in a satellite-derived whitecap database, Albert et al (2016) found that whitecaps were not dependent on wave parameters, but were actually modestly dependent on SST. They noted that the lack of dependence on wave parameters may have been a result of using wind history as a proxy for wave age and spatial averaging.…”
Section: The Effect Of Sstmentioning
confidence: 88%
“…This could potentially explain the difference between the value of c 1 we retrieved from our measurements and the one retrieved from the entire whitecap database. However, conversely, in a satellite-derived whitecap database, Albert et al (2016) found that whitecaps were not dependent on wave parameters, but were actually modestly dependent on SST. They noted that the lack of dependence on wave parameters may have been a result of using wind history as a proxy for wave age and spatial averaging.…”
Section: The Effect Of Sstmentioning
confidence: 88%
“…As shown in Figure 6b, the relationship between AOD and wind speed consists of two visible phases: AOD associated mainly with fine-mode aerosols at lower wind speeds and a distinct increase of larger aerosols that starts to occur around 3.5 m/s. Note, it is suggested that that white caps start to form at wind speeds of around 3.5 m s −1 [51][52][53][54]. Even so, the parameterizations derived in the first three studies for low wind speeds, 3-5 m s −1 , include whitecap fractions that differ by more than one order in magnitude [53].…”
Section: Evaluation Of Modis-derived Aod Versus Surface Wind Speedmentioning
confidence: 99%
“…Highly scattering non-aerosol targets on the ocean surface include whitecaps, foam and bubbles, sea ice, floating vegetation, high calcite waters, high sediment waters, optically shallow waters (e.g., with bright coral or sand) and regions with concentrated floating plastics (Frouin et al, 1996;Li et al, 2003;Marmorino and Smith, 2005;Balch et al, 2011;Dierssen et al, 2015;Fogarty et al, 2017;Perry et al, 2018). The most widespread of these is enhanced reflectance due to the production of whitecaps that occur over vast regions of the global ocean, particularly in the Southern Ocean (Albert et al, 2016). The heritage approach to mask whitecaps uses wind speed measurements to estimate the whitecap fraction, but such relationships are only climatological and do not predict instantaneous whitecap fields.…”
Section: Masking and Other Preliminary Necessitiesmentioning
confidence: 99%